Gamificación como estrategia didáctica en el proceso de enseñanza - aprendizaje de la asignatura inglés aplicado a los estudiantes de octavo año de educación básica en la Unidad Educativa “San Lorenzo”, cantón Guaranda, provincia Bolívar, periodo lectivo 2021 – 2022. - Monar Coloma, Julio César (2022)
The present work is focused on how gamification positively influences the learning of the English language in students in the eighth year of Basic Education, for this, it is necessary to know the factors that cause disinterest in the subject. In this way, a technological proposal is presented with the aim of solving the problem identified within the institution. The main purpose is to motivate students through a series of strategies integrated into a game that is attractive to students, reflected in its mechanics, such as levels or difficulties. It is necessary to emphasize that psychology plays a fundamental role in this process, since it enhances the individual's cognitive abilities, such as perception, memory and even their reflexes